70 anos da guerreira: a mestiçagem brasileira na tradução musical de Clara Nunes - Expedito Leandro Silva (Ciências Sociais Unisinos)
Clara Francisca Gonçalves Pinheiro. Stage Name: Clara Nunes. On August 12, 2012 this vigorous woman from Paraopeba in the state of Minas Gerais would have turned 70 years old. Her family life, in the context of culture and religion, contributed to her musical de- velopment from an early age broadening her contact with folk music. In this sense, her songs started dialoging with the world of samba and with the universe of African-Brazilian religions. Among the songs that best represent the artist portrayal are “Canto das Três Raças” and “Brasil Mestiço Santuário da Fé”, sang by her in the 1980s, the lyrics and interpretation showed the social Brazilian ethnological context in great detail. However, the cries of the people and the musical manifestation reproduced in the songs present an ideology of nationhood whose identity is the Brazilian miscegenation which means the cultures of the native Indians, the white and the black people.